2019
DOI: 10.17241/smr.2019.00493
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and Heart

Abstract: Scientific investigations in the past few decades have supported the important role of sleep in various domains of health. Sleep apnea is a highly prevalent yet underdiagnosed sleep disorder representing a valid cardiovascular risk factor, particularly for hypertension. While several studies have demonstrated the benefits of sleep apnea treatment on subclinical cardiovascular measures, there is a paucity of studies proving reduction of cardiovascular events and mortality. Sufficient and highquality sleep is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…Abnormal sleep duration and poor quality (eg, low sleep efficiency and obstructive sleep apnea [OSA]) can contribute to disturbed BP control and cardiovascular risks, such as hypertension. 9,10 Sleep architecture is an objective measure of sleep quality assessed by polysomnography (PSG). This parameter characterizes the distributions of different stages, and it can be broadly classified into two forms: rapid eye movement (REM) and non-rapid eye movement including N1, N2, and N3 stages (collectively NREM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal sleep duration and poor quality (eg, low sleep efficiency and obstructive sleep apnea [OSA]) can contribute to disturbed BP control and cardiovascular risks, such as hypertension. 9,10 Sleep architecture is an objective measure of sleep quality assessed by polysomnography (PSG). This parameter characterizes the distributions of different stages, and it can be broadly classified into two forms: rapid eye movement (REM) and non-rapid eye movement including N1, N2, and N3 stages (collectively NREM).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal sleep duration and poor quality (eg, low sleep efficiency and obstructive sleep apnea [OSA]) can contribute to disturbed BP control and cardiovascular risks, such as hypertension. 9,10 Sleep nographic data from 3,565 patients referred to an academic sleep center. BPV was calculated using the intra-individual coefficient of variation of BP measures collected 12 months before the sleep study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the overall pattern of nocturnal hypertension, studies have revealed that acute BP increases are triggered by obstructive respiratory events [2], arousals [11,12], leg movements [12] and transitions into the rapid eye movement (REM) stage of sleep [13]. Obstructive respiratory events related (hereafter 'respiratory') BP surge is of particular concern due to other concurrent pathophysiological consequences, such as exaggerated intrathoracic pressure change, as well as acute hypoxemia and hypercapnia, all of which synergistically and negatively impact the cardiovascular system [14]. As these BP surges may mediate the association of OSA with CVD, information about BP surges in sleep is important.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is associated with incident cardiovascular (CV) disease (CVD) and major adverse CV events among patients with CVD. [1][2][3][4] Obstructive apneas and hypopneas elicit an immediate CV response, including acute sympathetic surge and blood pressure (BP) increase. 56 Such CV responses are believed to be an important mediating mechanism of OSA's long-term association with adverse CV outcomes.…”
Section: Introductionmentioning
confidence: 99%